1998
DOI: 10.1046/j.1365-2672.1998.00473.x
|View full text |Cite
|
Sign up to set email alerts
|

Pyrrolnitrin from Burkholderia cepacia: antibiotic activity against fungi and novel activities against streptomycetes

Abstract: A bacterial strain identified as Burkholderia cepacia NB‐1 was isolated from water ponds in the botanical garden in Tübingen, Germany, and was found to produce a broad spectrum phenylpyrrole antimicrobial substance active against filamentous fungi, yeasts and Gram‐positive bacteria. In batch culture containing glycerol and L‐glutamic acid, the isolate NB‐1 produced the antibiotic optimally late in the growth phase and accumulated a main portion in their cells. Isolation and purification of the antibiotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
97
0
9

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(107 citation statements)
references
References 22 publications
1
97
0
9
Order By: Relevance
“…Burkholderia cepacia, the type species of the genus, was initially described as the causative agent of onion soft rot (Burkholder, 1950), but many strains belonging to the B. cepacia complex are also able to promote plant health (Parke & Gurian-Sherman, 2001). Similarly, other Burkholderia species have been reported to exhibit plant-growth-promoting or biocontrol effects (El Banna & Winkelmann, 1998;Tran Van et al, 2000;Estrada de los Santos et al, 2001). …”
mentioning
confidence: 99%
“…Burkholderia cepacia, the type species of the genus, was initially described as the causative agent of onion soft rot (Burkholder, 1950), but many strains belonging to the B. cepacia complex are also able to promote plant health (Parke & Gurian-Sherman, 2001). Similarly, other Burkholderia species have been reported to exhibit plant-growth-promoting or biocontrol effects (El Banna & Winkelmann, 1998;Tran Van et al, 2000;Estrada de los Santos et al, 2001). …”
mentioning
confidence: 99%
“…Para el caso de B. cepacia, ha sido considerada una bacteria con un potencial para el control biológico de hongos fitopatógenos (JAYASWAL et al, 1990). La actividad inhibitoria de esta bacteria contra una diversidad de fitopatógenos ha sido atribuida a la producción de metabolitos secundarios como cepacina, pirrolnitrina, altericidina y otros compuestos volátiles y no volátiles aun no identificados (EL-BANNA y WINKELMANN, 1998;QUAN et al, 2006).…”
Section: Información Soportada Por Mahenthiralingamunclassified
“…Studies on the mechanism of action of pyrrolnitrin showed that it probably blocks electron transfer between the dehydrogenases and the cytochrome components of the respiratory chain [29]. The introduction in the pentabromopseudilin of a carbonyl group between the phenyl group and the pyrrole moiety, i.e., compound 4 (Figure 1), entails an increase in antibacterial activity against Escherichia coli and Bacillus subtilis, whereas N-methylation is disadvantageous for the antibacterial activity [19,21].…”
Section: Halogenated Pyrroles Related To Pyrrolomycinsmentioning
confidence: 99%
“…Studies on the mechanism of action of pyrrolnitrin showed that it probably blocks electron transfer between the dehydrogenases and the cytochrome components of the respiratory chain [29]. …”
Section: Halogenated Pyrroles Related To Pyrrolomycinsmentioning
confidence: 99%
See 1 more Smart Citation